The role of relative humidity, temperature and substrates in the survival of Nasutitermes corniger - Pozo-Santiago, Cesár Orlando; Velázquez-Martínez, José Rodolfo; Torres-de la Cruz, Magdiel; De la Cruz-Pérez, Aracely; Capello-García, Silvia; Sánchez-Gutiérrez, Facundo; Pérez de la Cruz, Manuel (Ecosistemas y Recursos Agropecuarios, 2020)
The species Nasutitermes corniger (Motschulsky) is an arboreal termite, causes damage in urban and agricultural areas. Despite its economic importance, there are no studies on the basic aspects for its management in the laboratory, which will lay the foundations for the future development of control strategies. The objective of the study was to evaluate in the laboratory the survival of N. corniger at different conditions of relative humidity, temperature, humidity of the substrate and its preference for different types of wood. Relative humidities were tested between 9 and 100%, temperatures of 20, 25 and 30 ◦C, six substrates: pine, cedar, pink poui, eucalyptus, macuilís, coconut fiber and four substrate humidities of 0 to 60% were tested. The results indicate a significant effect on all the variables measured. The highest survival of N. corniger was had with a relative humidity of 100%, a temperature of 20 ◦C and a humidity of the substrate of 60%, while the most preferred substrate was eucalyptus. In the appropriate percentages, the interaction of these three factors provides the best conditions for the survival of N. corniger.